PkMD Kue Pisang Lanna Ibu-Ibu Pkk Kecamatan Parang Loe Kabupaten Gowa - Salmayati Salmayati; Kasma Amin (Fakultas Sastra - Universitas Muslim Indonesia, 2017)
PkMD Lanna Banana cake is to help the community in providing skills in managing banana fruit ingredients into Lanna banana cakes which are of high value, delicious, and beneficial for the community. PkMD Kue Banana Lanna done by the community can innovate with various taste buyers, namely chocolate and cheese to attract attention, both local and foreign tourists and can popularize the name of the region, especially in the Lanna Village. Because the banana cake labeled Lanna banana cake can also be used as a home industry with a background of processed bananas making it a business opportunity for the Village Community inUMI, Lanna Village, Parangloe Subdistrict. starting from the selection of good and quality banana ingredients, processing bananas that make the ingredients for baking, the process of making cakes from the materials used and the use of supporting equipment during the activity process, packaging cakes with attractive packaging as the attractiveness of buyers, to distribution to various shops and reach consumers. This skill is expected to help PKK mothers to create jobs for housewives who do not have fixed income while the knowledge provided can be continued to the younger generation who want to become competent entrepreneurs and can compete in local and global markets.